NATIONALISM FOR CONTEMPORARY INDONESIA: A STUDY ON Y.B. MANGUNWIJAYA’S DURGA UMAYI AND BURUNG-BURUNG RANTAU - Elisabeth Oseanita Pukan; Heri Setyawan (Sintesis, 2022)
Literary works have the potential to function as a social document, outlining social history. Because of that, social picture can be abstracted from literature. This research delves into Mangunwijaya's novels “Durga Umayi” and “Burung-Burung Rantau” to examine the concepts of nationalism. The textual analysis of the narratives is done through identification of symbols and allusion, and the stories are perceived as national allegories. Theories of symbol, allusion, and allegory by Johnson Arp and Harmon Holman are utilized in the textual analysis. To draw the abstraction about nationalism, the researchers refer to Benedict Anderson’s theory. In the “Durga Umayi”, through the character of Iin Sulinda Pertiwi Nusamusbida, Mangunwijaya shows in achieving independence of the country, individuals involved are vulnerable. They can turn bitter and lose their purpose, even sell their own nation. Meanwhile, in “Burung-Burung Rantau”, Mangunwijaya shows the different characters in engaging to nationalism. The protagonist, Neti, exemplifies the idea of nationalism through her critical outlook on her own tradition. She opens herself to global values and derive from it good practices to be applied in her own country, Indonesia. The two narratives suggest that people must have a sense of allegiance to their nation while being critical, and they must understand their duties on the world stage. Additionally, that sense of nationalism must be shown through solidarity with one's fellow citizens, particularly the impoverished one.